Cognitive impairment along the course of depression: non-pharmacological treatment options - Listunova, Lena; Roth, Corinna; Bartolovic, Marina; Kienzle, Johanna; Bach, Claudia; Weisbrod, Matthias; Roesch-Ely, Daniela (Psychopathology, 2018)
Major Depressive Disorder (MDD) is one of the most common psychiatric disorders, with a large global impact on both the individual and the society. In this narrative review, we summarize neurocognitive deficits during acute and (partially) remitted states of depression. Furthermore, we outline the potential negative effect of cognitive impairment (CI) on functional recovery, and discuss the role of several variables in the development of CI for MDD patients. Though there is cumulating evidence regarding persistent CI in unipolar depression, research on treatment options specific for this patient group is still scarce. Hence the central aim of our review is to present non-pharmacological interventions, which are thought to reduce CI in affected MDD patients. We discuss cognitive remediation therapy (CRT), physical exercise, yoga, mindfulness-based therapy, and modern neuromodulation approaches like neurostimulation and neurofeedback training. In conclusion, we propose future directions for research on CI in depression. Looking further ahead, we suggest creative interventional designs that include a direct comparison of different non-pharmacological treatment approaches on neurocognition and functional outcome of MDD. Furthermore, additive and synergistic effects of CRT with other treatment approaches should be examined and compared to create multimodal and even personalized intervention programs.